2014
DOI: 10.16970/ted.08838
|View full text |Cite
|
Sign up to set email alerts
|

Fitness of Bactrocera dorsalis (Hendel) on seven host plants and an artificial diet

Abstract: Fitness of Bactrocera dorsalis (Hendel) on seven host plants and an artificial dietBactrocera dorsalis (Hendel)'in yedi konukçu bitki ve bir yapay besin üzerindeki performansı

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…'Tommy Atkins' mango at ambient conditions (25 ± 1 • C, 65 ± 5% RH) to hatch was 2 days. This finding is comparable to results of previous studies that reported an average of 1.2 ± 0.02 days [49], 1-2 days [50], 2-3 days [37], and 3 days [51]. The slight variances in the above findings are probably due to differences in the incubation temperature, host material, and experimental procedure, which are known to influence the development and performance of stages of B. dorsalis [47,52].…”
Section: Discussionsupporting
confidence: 89%
“…'Tommy Atkins' mango at ambient conditions (25 ± 1 • C, 65 ± 5% RH) to hatch was 2 days. This finding is comparable to results of previous studies that reported an average of 1.2 ± 0.02 days [49], 1-2 days [50], 2-3 days [37], and 3 days [51]. The slight variances in the above findings are probably due to differences in the incubation temperature, host material, and experimental procedure, which are known to influence the development and performance of stages of B. dorsalis [47,52].…”
Section: Discussionsupporting
confidence: 89%
“…dorsalis adults reared with an artificial diet, although B . dorsalis females had a host preference for oviposition and their reproduction was affected by the host plants they had grown [ 30 ]. We improved the current OM using a two-phase OM and precisely estimated egg production under various temperatures, especially lower temperature conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They were reared on an artificial diet for more than 200 generations in TARI. Insects were reared according to the method of Huang and Chi [ 30 ] based on an artificial diet developed by Tanaka et al [ 47 ]. Pupae were placed in a plastic netted cage (30 x 30 cm) and emerged as adults, who were then fed an artificial diet composed of 200 g Yeast Hydrolysate Enzymatic (MP Biomedicals, LLC., Illkirch-Graffenstaden, France), 40 g granulated sugar, 10 ml protein hydrolysate (Alco Standard Co., Pennsylvania, USA), and 50 ml water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations